An amphiphilic invertible polymer as a delivery vehicle for a M2e-HA2-HA1 peptide vaccine against an Influenza A virus in pigs. Issue 31 (18th July 2019) - Singh, Gagandeep; Zholobko, Oksana; Pillatzki, Angela; Webb, Brett; Nelson, Eric; Voronov, Andriy; Ramamoorthy, Sheela
Abstract: Influenza A viruses (IAVs) are a group of genetically diverse and economically important zoonotic pathogens. Despite decades of research, effective and broadly protective vaccines are yet to be developed. Recent breakthroughs in epitope-based immunization for influenza viruses identify certain conserved regions of the HA2 and M2e proteins as capable of inducing broad protection against multiple influenza strains. The M2e and HA2 peptides have been evaluated in mice but not as a combination in pigs, which play an important role in the transmission and evolution of IAV. Peptides are inherently weak immunogens; and effective delivery of peptide antigens is challenging. To enhance the delivery and immunogenicity of peptide-based vaccines, the conserved M2e and HA2 and a strain-specific HA1 epitope of Influenza A (H1N1) pdm09 were expressed as a chain in a bacterial expression system and entrapped in a novel amphiphilic invertible polymer made from polyethyelene glycol (PEG, molecular weight 600 g/mol) and polytetrahydrofuran (PTHF, molecular weight 650 g/mol), PEG600 PTHF650 . Piglets vaccinated with polymeric peptide vaccine mounted significantly stronger antibody responses against the peptide construct when compared to piglets immunized with the multi-epitope peptide alone. When vaccinated pigs were challenged with Influenza A (H1N1) pdm09, viral shedding in nasal secretions and lung lesion scores were significantly reduced when compared to the unvaccinated controls and pigs vaccinated with the peptide alone at six days post-challenge. Thus, the combination of the PEG600 PTHF650 polymer and trimeric peptide construct enhanced delivery of the peptide antigen, acted as an adjuvant in stimulating strong antibody responses, reduced the effects of viral infection in vaccinated pigs.